A look to the Electricity Generation from Non-Conventional Renewable Energy Sources in Colombia - Eras, Juan Jose Cabello; MorejÃ³n, Milen Balbis; GutiÃ©rrez, Alexis Sagastume; GarcÃa, Aldo Pardo; Ulloa, Mario Cabello; MartÃnez, Francisco Javier Rey; Rueda-Bayona, Juan Gabriel (International Journal of Energy Economics and Policy, 2018)
This study discusses the potentialities and current situation of the electricity generation from non-conventional renewable energy sources (NCRES) in Colombia. In particular, three scenarios considering the increment of NCRES electricity based generation installed capacity are discussed. The three scenarios are compared to the 2020 forecast of the Energy and Mining Planning Unit ((UPME). Overall, it id shown that Colombia has a significant unused NCRES potential, which makes possible to realize the 6% target for NCRE based electricity generation capacity installed by 2020. In particular, the photovoltaic energy is foresee to account for over half of the NCRE mix. Even though the law 1715 is a progress towards integrating NCRE to the National Electric System, more policies and developments are required, to further the NCRE based installed generation capacities. Keywords: Non-conventional renewable energy (NCRE), electricity generation, energy policy JEL Classifications: O, Q4, Q42 DOI: https://doi.org/10.32479/ijeep.7108